Exercise Equipment for Thai Healthy Lifestyle - Seerasungnern, Surin; Kemprakhon, Prasert (Journal of Health Science of Thailand, 2017)
Exercise is useful for health promotion and disease prevention. Proper and regular exercise together with diet control and rational use of drugs can prevent disease and reduce complications. Nhongchaisie Subdistrict Health Promoting Hospital has set up a team to demonstrate and educate on exercise while waiting for examination by a physician; and invented a model of equipment for exercise based on the Thai Health Life Style concept with the objective to promote health, prevent complications and rehabilitate physical conditions among patients with diabetes, hypertension and stroke. The exercise set was produces from left-over materials, and it could be applied in for use in households and communities. The single exercise set was comprised of 5 different items placed on a 1.79x0.95 platform. It could be used for muscle exercise from head to toe, and facilitate the body system including blood circulation, respiration, strengthening muscles and expanding the joint movement. Assessment of effectiveness and work quality of the equipment by a physical therapist through the test with 145 patients during October 2012 – January 2013 revealed satisfaction from 95.68 percent of the patients.